2017
DOI: 10.1021/acsnano.7b04079
|View full text |Cite
|
Sign up to set email alerts
|

Superposition Principle in Auger Recombination of Charged and Neutral Multicarrier States in Semiconductor Quantum Dots

Abstract: Application of colloidal semiconductor quantum dots (QDs) in optical and optoelectronic devices is often complicated by unintentional generation of extra charges, which opens fast nonradiative Auger recombination pathways whereby the recombination energy of an exciton is quickly transferred to the extra carrier(s) and ultimately dissipated as heat. Previous studies of Auger recombination have primarily focused on neutral and, more recently, negatively charged multicarrier states. Auger dynamics of positively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 47 publications
10
112
1
Order By: Relevance
“…These time constants are assigned to the X – lifetimes ( τ X – ) of DIRs, which should contain contributions from both radiative and nonradiative Auger recombinations. According to previous reports, 48 , 70 72 the radiative lifetime of X – ( τ X – ,r ) is ∼1/1.7 that of single excitons ( τ X ) for CdSe@CdS systems, with τ X already determined from time-resolved PL measurements (Fig. S3b † ).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…These time constants are assigned to the X – lifetimes ( τ X – ) of DIRs, which should contain contributions from both radiative and nonradiative Auger recombinations. According to previous reports, 48 , 70 72 the radiative lifetime of X – ( τ X – ,r ) is ∼1/1.7 that of single excitons ( τ X ) for CdSe@CdS systems, with τ X already determined from time-resolved PL measurements (Fig. S3b † ).…”
Section: Resultssupporting
confidence: 56%
“…The QYs are in the range of 14% to 24% and are relatively higher in DIRs with more strongly delocalized electron wavefunctions (2.6 nm@thin and 3.4 nm@thick) or with large volume (4.2 nm@thick). These QYs might explain the “gray” states observed in single-particle PL experiments of CdSe@CdS NRs 73 as the photocharged species, usually being X – for CdSe@CdS systems, 70 are reasonably bright rather than completely dark.…”
Section: Resultsmentioning
confidence: 98%
“…[31][32][33][34][35][36][37] The radiative trion emission lifetime constant (k r,X± ) is easily obtained by the core emission lifetime constant, as theoretically determined from k r,X± = 2•k r,X (See the Supporting information for details). [32,[35][36] The relative PL QY is 98% for InP/5ZnSe/ZnS and 95% for InP/10ZnSe/ ZnS. The core emission lifetime of neutral QDs is 33 ns for InP/5ZnSe/ZnS and 35 ns for InP/10ZnSe/ZnS.…”
Section: Time-resolved Photoluminescence Decay and Their Kinetic Tracesmentioning
confidence: 99%
“…Several previous studies have reported that the Auger recombination rate of positive trion is faster than that of negative trion. [31,36,38] Meanwhile, Hou et al have recently described in detail the crossover of Auger recombination rates of negative and positive trions in CdSe/CdS QDs. [34] In QDs with a thin shell, the wavefunction of conduction band maximum (CBM) extends to the region where dielectric screening is much weaker.…”
Section: Time-resolved Photoluminescence Decay and Their Kinetic Tracesmentioning
confidence: 99%
“…CuSCN has been used in perovskite solar cells to extract photoexcited holes from the perovskite layer [47,48]. Thus, a negatively charged NC is formed upon addition of CuSCN due to the extraction of photogenerated holes from the NCs, i.e., CuSCN enables photochemical doping of perovskite NCs [49,50]. In Figs.…”
Section: A Single-dot Spectroscopy Of Fapbbr 3 Ncsmentioning
confidence: 99%